Taxation of Goods and Services from 1862 to 2010 - Mikael Stenkula (Research Institute of Industrial Economics (IFN), 2013)
This paper presents annual Swedish time series data on consumption taxes, i.e. the indirect taxation of goods and services, between 1862 and 2010. As a share of total state tax revenues, consumption taxes were very high at the beginning of the period, though as a share of GDP it was rather low. At this time, customs duties and specific consumption taxes on alcohol and sugar were the most important tax revenues. The importance of consumption taxes decreased during the World Wars, in particular during World War I. However, between the Wars the consumption taxes were still important and vehicle taxation as well as tobacco taxation now also contributed significantly to the tax revenues. After World War II and the 1940s, the tax revenues from consumption taxes has increased slightly again. However, as a share of GDP it increased sharply. On the other hand, importance of specific consumption taxes and, in particular, customs duties has fallen dramatically. The mix of the specific consumption taxes has also changed with and increased emphasis on energy and environmental taxes. A permanent general consumption tax was introduced in 1960 and its importance has increased sharply since then.
Keywords: H20; N43; N44; 330; Consumption taxes; Taxation of goods and services; Excise duties; Customs duties; VAT